Multiple sclerosis: I. Monocyte stimulatory defect in mixed lymphocyte reaction associated with clinical disease activity. - Baxevanis, C N (1987)
To investigate whether abnormalities of cellular immune responses are associated with multiple sclerosis (MS), we tested peripheral blood mononuclear cells (PBMC) or T cells, and monocytes from MS patients as responder and stimulatory cells respectively, in the allogeneic (allo-MLR) and autologous mixed lymphocyte reaction (auto-MLR). We found that PBMC or T cells from all MS patients were able to develop strong proliferation against allogeneic monocytes derived from normal individuals. Moreover, the capacity of monocytes from MS patients to act as accessory cells for autologous T cells in the allo-MLR was indistinguishable from that of normal donors. In contrast, monocytes from patients with active MS were not able to stimulate responder cell proliferation either in allo-MLR or in auto-MLR. This monocyte defect was partially restored in the inactive stage of the disease. In conclusion our results show that the stimulatory capacity of monocytes from MS patients in the MLR is closely associated with the clinical stage of MS. The observed monocyte defect may be helpful in understanding the pathogenesis of MS and can be used in evaluating the outcome of the disease activity.